(3GdJPcQI GdMeOhfjIs - (3eMeO Hf GdMSf Hf eMeO Hf Ydj Hf MeOhf, CHh GdeYGdj, HgGA GdOjf GdHZOGOj,J (B562 (3g` s
(3ChdgG (B:s
(3GdHGH GdKGdK hGdCQHYjf ai GdcfGjI hGdJYQjV s
(3BNQgG (B:s
(3GdSGOS hGdCQHYjf ajeG LGA ai ai GdehGcdI hGdJWajd s
(3fSNI KGefIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B85 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B217s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B21 - (3U (B436 s
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK (B(2948) s
Keywords: (3GdCOHs